Noun Formation with Reference to The Articles on Politics Published in Jakarta Globe Newspaper - Ni Made Utari Handayani; I Gusti Ayu Gde Sosiowati; Putu Lirishati Soethama (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The title of the study which is “Noun Formation with Reference to Articles on Politics published in Jakarta Globe Newspaper” is aimed at investigating the kinds and functions of derivational suffixes forming nouns and how the meaning of derivation words is represented in the sentence. The data were taken from the online newspaper The Jakarta Globe. The method used in collecting the data was documentation method and a note-taking technique. The descriptive qualitative approach was used in analyzing the data. The theory applied to analyze the data was the theory of Morphology proposed by Plag (2018) and Bauer (1983). In addition, Oxford’s Learner Dictionary was used to classify the word class and the meaning of derivation words. The result shows that there were twelve kinds of nominal suffixes found, namely suffix ship/, /-ance/ (and its variant ence,), /-ism/, /-ity/, /-er/ (and it’s variant or), /-ant/, /-ce/-cy/, /-ing/, /-ion/( with its variant –action, -ification), /-ee/, /-an/ (with its variant –ean, -Ian), and /-ment/. There were two functions of derivational suffixes: class-maintaining derivation of nouns from nouns and class-changing derivations, such as nouns from verbs and adjectives. The meaning of the derivation words is based on the context of the sentence.